Analisis Perspektif Hukum Internasional Terkait Willow Project yang Berdampak Bagi Iklim Dunia - Lewlandy Lewlandy; Ibra Fulenzi Amri; Nadya Christina; Josua Bona Pangaribuan (Journal on Education, 2023)
Each country in carrying out its government must have certain goals, in general countries are oriented and focused on national interests that lead to the welfare and prosperity of the country. an agenda carried out by the United States (United States of America) as a national strategic project, namely the Willow Projects, this is a domino effect from Saudi Arabia (Kingdom Saudi Arabia) joining an association of multilateral cooperation of countries in various fields that are developing and leading namely BRICS (Brazil, Russia, India, China and South Africa). Saudi Arabia, which is the main partner in relation to the U.S. oil trade as a provider of oil trade, is now turning around to cooperate with BRICS. The impact of this happening was that the United States cheated by becoming the Willow Projects to be the solution to this problem in the midst of an international political dilemma. The Willow Projects is a United States drilling project carried out in the state of Alaska, this has an impact on the international world environment, if it is not governed by appropriate environmental law regulations. In conducting a scientific research, researchers use a method, namely the Empirical Normative method using a statutory approach.